Planifier avec le territoire : la dynamique des lieux de projets à l’épreuve des approches participatives et paysagères - Benoît Dugua; Leila Chakroun (VertigO)
Since the late 1990s, the soaring issues related to sustainability coupled with the ongoing process of metropolization have generated a progressive renewal of territorial planning methods. These new methods result primarily from the reconsideration of the conventional center/periphery divide and from the subsequent transformation of the relationship between the city and its territory, and between built-up and open spaces. In that context, participatory and landscape approaches rapidly gained legitimacy in the planning process, which has led to a significant change in the dynamics within and between project places. Recent works underline the importance of taking transactional places into account. Those places represent intermediary spaces of cooperation, enabling new synergies between the territory and politico-administrative stakeholders, experts and the inhabitants. In this article, we propose to enrich this concept of “transactional places” through two major themes : urban quality of life and urban agriculture. We illustrate the latter by means of two case studies in the agglomeration of Lausanne : the Boveresses neighbourhood contract and the participative design of the Agroecological Farm of Rovéréaz. To which extent the participatory and landscape approaches adopted in those places alter, even shift, the conventional dynamics of project places ? How does the peculiar dynamics of those places resonate with the different territorial levels within the agglomeration ?